Seismic effect on precast concrete structure for beam to column connection - Liew, Ming Hui, 1982-; Karim Mirasa, supervisor; Azlan Adnan; Fakulti Kejuruteraan Awam (2008)
Thesis (Sarjana Kejuruteraan (Awam - Struktur)) - Universiti Teknologi Malaysia, 2008